3 Residential exposure to fine particulate matter air pollution is associated with impaired cardiac phenotypes in dilated cardiomyopathy. (17th July 2020) - Tayal, Upasana; Fecht, Daniela; Chadeau, Marc; Gulliver, John; Ware, James; Cook, Stuart; Prasad, Sanjay
Abstract : Background: Air pollution might contribute to adverse ventricular remodelling in healthy populations. A recent study on a cohort of 500, 000 participants (UK Biobank) showed that residential exposure to particulate matter with aerodynamic diameter <2.5 μm (PM2.5) and nitrogen dioxide (NO2) was associated with cardiac chamber dilatation and increased left ventricular mass. Dilated cardiomyopathy (DCM) has marked structural and functional phenotypic heterogeneity. The biological basis for this is undefined, but environmental factors are plausible phenotypic modifiers. We sought to evaluate whether air pollution could be an important environmental modifier in DCM. Methods: Prospectively recruited patients with DCM underwent advanced phenotyping by cardiac magnetic resonance. Patients were followed up for the primary composite end-point of cardiovascular mortality, major arrhythmic events and major heart failure events. Long-term air pollution exposure estimates prior to the year of DCM diagnosis were assigned to each residential postcode centroid (on average 12 households). Annual average maps were available for NO2 concentrations in 2009 at 200m resolution and PM2.5 in 2010 at 100m resolution. Postcode centroids (x, y locations) were overlaid with each air pollution surface to obtain NO2 and PM2.5 estimates for each postcode and concentrations extrapolated to the year of diagnosis using information from the national air pollution monitoring network. Results: From the total cohort of 716 DCM patients enrolled to the study, 678 patients had postcodes which could be assigned a geographical location and air pollutant estimates. The median PM2.5 concentration was 15.4 (14.3 – 16.3) μg/m3 and the median NO2 concentration was 32.4 (24.1 – 40.6) μg/m3. Higher residential exposure to PM2.5 and NO2 was associated with increased left ventricular mass in DCM patients (table 1 ). Higher residential exposure to NO2 was associated with reduced left ventricular ejection fraction (Table 1 ). There was no association between exposure to PM2.5 levels or NO2 levels and cardiovascular outcomes (NO2 Hazard ratio 0.99, 95% confidence intervals (CI) 0.98-1.01, p= 0.90; PM2.5 hazard ratio 1.0, 95% CI 0.89-1.25, p= 0.54). Conclusion: Fine particulate matter air pollution has an adverse effect on cardiovascular phenotypes amongst patients with DCM suggesting air pollutants could be an environmental modifier of DCM. There was no apparent effect of fine particulate matter on major cardiovascular outcomes in this cohort. Future studies should explore whether air pollution contributes to DCM amongst at risk individuals. Conflict of Interest: None